Accelerating Alzheimer's disease drug innovations from the research pipeline to patients. Issue 6 (18th April 2018) - Goldman, Dana P.; Fillit, Howard; Neumann, Peter
Abstract: In June 2017, a diverse group of experts in Alzheimer's disease convened to discuss how to accelerate getting new drugs to patients to both prevent and treat the disease. Participants concluded that we need a more robust, diversified drug development pipeline. Strategic policy measures can help keep new Alzheimer's disease therapies (whether to treat symptoms, prevent onset, or cure) affordable for patients while supporting innovation and facilitating greater information sharing among payers, providers, researchers, and the public, including a postmarket surveillance study system, disease registries, innovative payment approaches, harmonizing federal agency review requirements, allowing conditional coverage for promising therapeutics and technology while additional data are collected, and opening up channels for drug companies to communicate with payers (and each other) about data and outcomes. To combat reimbursement issues, policy makers should address the latency time between potential treatment—which may be costly and fall on private payers—and societal benefits that accrue elsewhere.